Comparison of Transfer Process Layout at Company a using Arena Simulation Software - Muhammad Izzat Hakimi Ramlan; Tengku Nur Azila Raja Mamat; Shaiful Rizal Masrol (Progress in Engineering Application and Technology, 2024)
This study aims to analyze, provide ideas and compare two processes of transporting palm fruits from plantations to factories, which is the use of roads and cableway system. It have been conducted at a small scale palm oil factory Company A where the palm mill capacity is 5 metric tan/hour where the final product divided into two product which is crude palm oil and kernel. The lack of information about the previous study is one of the problem that need to be faced to conduct this study. The study was done by only focusing on the layout of the palm fruit transfer process, where the study will be conducted by using the Arena Simulation software to gather all the result. By using simulation, the results show a comparison between the two layout transfer processes where the analysis shows that the choice between these two processes requires careful consideration between the time and cost factors but based on the proposed layout simulation shows a reduction in time of 4% compared to the existing layout arrangements which can help in terms of further productivity. This study may have long-term benefits, including cost reduction and increased operational efficiency.